The Relationship Between Adverse Childhood Experiences and Alzheimer's Disease: A Systematic Review - Corney, Kayla B.; West, Emma C.; Quirk, Shae E.; Pasco, Julie A.; Stuart, Amanda L.; Manavi, Behnaz Azimi; Kavanagh, Bianca E.; Williams, Lana J. (Frontiers in Aging Neuroscience, 2022)
BACKGROUND: Alzheimer’s disease is a global health concern, and with no present cure, prevention is critical. Exposure to adverse childhood experiences may increase the risk of developing Alzheimer’s disease. This systematic review was conducted to synthesise the evidence on the associations between adverse childhood experiences (<18 years) and the risk of Alzheimer’s disease in adulthood. METHODS: A search strategy was developed and conducted to identify articles investigating the associations between exposure to adverse childhood experiences and the onset of Alzheimer’s disease by searching key databases (CINAHL, MEDLINE and PsycInfo). Two reviewers independently determined the eligibility of studies according to pre-determined criteria, and assessed the methodological quality using the US National Heart, Lung and Blood Institute 14-item checklist for observational cohort and cross-sectional studies, respectively. Due to limited studies, a descriptive synthesis was performed. The protocol for this review is published in BMJ Open and registered with PROSPERO (CRD42020191439). RESULTS: Our search yielded 781 articles, of which three (two separate analyses from the same cohort study and one cross-sectional study) met the predetermined eligibility criteria. The methodological quality assessment yielded an overall mean score of 78.9% (range 66.6 – 84.6%). All studies found adverse childhood experiences were associated with an increased risk of Alzheimer’s disease. However, there was a limited number of available studies to inform the synthesis. CONCLUSIONS: Adverse childhood experiences appear to be associated with an increased risk of Alzheimer’s disease, although, further research is needed.